POLA TANAM BERBASIS JARAK PAGAR - Herman, Maman; Anam, Choirul (Universitas Islam Darul Ulum, 2009)
In research conducted with the cropping pattern used between maize and chili plants showed that the distance the fence is relatively less able to compete with corn. The use of maize as a crop during the growth of jatropha causes disturbed and the production had decreased by 90%, whereas between corn plants can grow normally and can produce seven tonnes of dry loose maize per hectare. As with the use of pepper plants interrupted, growth and productivity of Jatropha plant is not susceptible to interference, while the chili plant capable of producing 110 g / ph. This shows that the distance the fence is not tolerant of shade so as to alternate between the plants, is necessary to find plants that are shorter than the distance the fence and have high economic value. Planting distance between the ideal plants is one meter from the plant jatropha. If the distance is less than one meter cropping, the effect of shading and nutrient competition will be very detrimental to both the growth of jatropha plants and productivity. Therefore, in designing the planting pattern must be known in advance of plant characters that will be used to achieve the synergy between plants.